Treatment of tequila vinasse and elimination of phenol by coagulation–flocculation process coupled with heterogeneous photocatalysis using titanium dioxide nanoparticles. Issue 8 (2nd April 2020) - Arreola, Alicia Rodriguez; Tizapa, Marciano Sanchez; Zurita, Florentina; Morán-Lázaro, Juan Pablo; Valderrama, Rocío Castañeda; Rodríguez-López, José Luis; Carreon-Alvarez, Alejandra
ABSTRACT: In this research, we are reporting the treatment of tequila vinasse by a coagulation–flocculation process coupled with heterogeneous photocatalysis using two types of titanium dioxide nanoparticles, i.e. (1) commercial nanoparticles, and (2) nanoparticles synthesized by sol–gel. The efficiency in the elimination of phenol, which is one of the most harmful contaminants in tequila vinasse, was also included in the evaluation of the treatment process. The synthesized titanium dioxide nanoparticles were annealed in air at 400°C for 1 h and were characterized by X-ray diffraction, transmission electron microscopy, ultraviolet-visible and Raman spectroscopy. Anatase phase was observed in both samples, with a crystallite size of 22.5 and 9.8 nm for commercial and synthesized nanoparticles respectively. Tequila vinasse was characterized before and after the treatments by measuring physicochemical parameters such as pH, chemical oxygen demand (COD), colour, total suspended solids (TSS), as well as using ultraviolet-visible spectroscopy and Raman spectroscopy to identify the presence of organic compounds, and gas chromatography (GC) for phenol quantification. Raw vinasse was treated initially by coagulation–flocculation producing clarified vinasse, which in turn was treated by photocatalysis for 3 h using hydrogen peroxide as oxidizing agent. The use of synthesized titanium dioxide nanoparticles allowed the highest efficiencies, reaching reductions of 99.4%, 86.0%, and 70.0% for TSS, colour, and COD respectively. GC results showed the reduction of phenol concentrations in 89.7% with our synthesized nanoparticles in contrast to 82.7% reduction, with commercial titanium dioxide nanoparticles. GRAPHICAL ABSTRACT: